Conceptualization of Manggarai society on power relationship in marriage kinship - BUSTAN, F; SEMIUN, A.; BIRE, J. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study investigates the conceptualization of Manggarai society on power relationship between wife giver and wife taker in marriage kinship. The theoretical framework used in the study is eclectic as it amalgamates a number of conceptions proposed in social anthropology, sociolinguistics and cultural linguistics. The relationship of power between Anak Rona (wife giver) and Anak Wina (wife taker) is asymmetrical, as the Anak Rona as wife giver holds higher power than the Anak Wina as wife taker. The asymmetrical relationship of their power is realised in the forms and meanings of the language they employ in many verbal expressions. RESUMEN Este estudio investiga la conceptualización de la sociedad Manggarai sobre la relación de poder entre la esposa dadora de familia y la esposa tomadora de familia en el parentesco matrimonial. El marco teórico utilizado en el estudio es ecléctico, ya que combina varias concepciones propuestas en antropología social, sociolingüística y lingüística cultural. La relación de poder entre anak rona (esposa dadora) y anak wina (esposa tomadora) es asimétrica, ya que anak rona como esposa dadora tiene mayor poder que la anak wina como esposa tomadora. La relación asimétrica de su poder se realiza en las formas y significados del lenguaje que emplean en muchas expresiones verbales.